Evaluación de dosis y métodos de aplicación de azufre y su efecto residual en el cultivo de maíz en dos localidades de Azuero, Panamá - Gordon, Roman; González, Andrés; Franco, Jorge; De Gracia, Nivaldo; de Herrera, Adys; Raun, William (Agronomía Mesoamericana, 2016)
Two trials were conducted in 1990 in the zone of Azuero-Panama, to observe the response of the corn to the residual effect of sulphur (CaS04) under two application methods. In 1989, sulphur was broadcasted at arate of 0.20, 40 and 80 kg/ha, or handspiked at arate of 0.20 and 40 kg/ha. During the second cycle (1990), only 100 kg/ha of N were applied to the plots in order to observe the residual effect of the treatments. There was a lineal response for the two bypsum application methods in the first cycle, but there was no interaction among these two independent variables. The fact that one of the. highest yields wasobtained with a 20 kg/ha, doseshows us that a low dosage of this element is anough to have significant responses. The resiudal response of the sulphur application (1990) was highly significant getting yield increments ranging from 0.483 to 1.682 t/ha. The economic analysis of the two cycles (1989-1990) showed that the sulphur application was profitable with respect to the dose 0 (zero), given the low cost of the agricultural gypsum.